Comparative genomics and transcriptomics insight into myxobacterial metabolism potentials and multiple predatory strategies - Wang, Chunling; Xiao, Yi; Wang, Yong; Liu, Yumin; Yao, Qing; Zhu, Honghui (Frontiers in Microbiology, 2023)
Myxobacteria are part of the phylum Myxococcota, encompassing four orders. Most of them display complex lifestyles and broad predation profiles. However, metabolic potential and predation mechanisms of different myxobacteria remains poorly understood. Herein, we used comparative genomics and transcriptomics to analyze metabolic potentials and differentially expressed gene (DEG) profiles of Myxococcus xanthus monoculture (Mx) compared to coculture with Escherichia coli (MxE) and Micrococcus luteus (MxM) prey. The genomic analysis showed that myxobacteria had conspicuous metabolic deficiencies, various protein secretion systems (PSSs) and the common type II secretion system (T2SS). RNA-seq data demonstrated that M. xanthus overexpressed the potential predation DEGs, particularly those encoding T2SS, the tight adherence (Tad) pilus, different secondary metabolites (myxochelin A/B, myxoprincomide, myxovirescin A1, geosmin and myxalamide), glycosyl transferases and peptidaseduring predation. Furthermore, the myxalamide biosynthesis gene clusters, two hypothetical gene clusters and one arginine biosynthesis clusters were highly differential expressed in MxE vs MxM. Additionally, comparative genomics indicated that homologue proteins of the Tad (kil) system and five secondary metabolites were in different obligate or facultative predators. Finally, we provided a working model for exhibiting multiple predatory strategies when M. xanthus prey on M. luteus and E. coli. The study might spur application-oriented research on the development of novel antibacterial strategies.